IBNU KHALDUN DAN PENDIDIKAN ISLAM: TELAAH ATAS AL-MUQADDIMAH - Nova Saputra, Enggal Bagas; Saiddaeni, Saiddaeni; Bistara, Raha (STIT Sunan Giri Bima, 2024)
This study aims to examine Ibn Khaldun's thoughts on the concept of education as outlined in his book titled Muqaddimah. The research method used is a literature review of the primary source, the Book of Muqaddimah, supported by other sources such as journal articles, research results, and findings which are then analyzed to draw conclusions. The results of the study indicate that Ibn Khaldun paid significant attention to the field of education in addition to his expertise in sociology. In his monumental work, Muqaddimah, Ibn Khaldun elaborates on various aspects of education, including the nature of education itself, the classification of knowledge, the goals of education/teaching, effective teaching methods, stages of education, and the integration of religious knowledge with rational sciences. Ibn Khaldun refutes the dichotomy of knowledge by striving to understand revelation with the help of reason/intellect. To this day, the educational concepts formulated by Ibn Khaldun remain relevant and can be applied to the modern educational era, which emphasizes affective, cognitive, and psychomotor aspects. Ibn Khaldun's concept of education in the Muqaddimah encompasses these three important aspects of modern education. Ibn Khaldun's thoughts on education in the Muqaddimah have implications for modern education, as evidenced by his concepts on educational goals, teaching methods, curriculum, and educators in the Muqaddimah, which have implications for modern education.